Association between asymmetry in cataract and asymmetry in age-related macular degeneration. The Beijing Eye Study - Xu, Liang; Sheng You, Qi; Cui, Tongtong; Jonas, Jost B. (Graefe's archive for clinical and experimental ophthalmology, 2011)
Background To examine in an intra-individual comparison whether cataract is associated with age-related macular degeneration (AMD). Methods The population-based Beijing Eye Study included 4,439 subjects (age: 40+ years) out of 5,324 subjects invited to be examined. Using lens and fundus photographs, the amount of AMD was graded according to the Wisconsin Age-Related Maculopathy Grading system and the degree of cataract was graded using the system of the Age-Related Eye Disease Study. Results Photographs with sufficient quality for bilateral examination of the lens and macula were available for 3,826 (86.2%) participants with a mean age of 55.3 ± 10.0 years (range: 40–90 years) and a mean refractive error of −0.38 ± 2.18 diopters (range: −20.13 diopters to +7.50 diopters). The side difference in presence of early AMD and late AMD respectively was not significantly associated with the inter-eye difference in the amount of nuclear cataract [ P = 0.27 and P = 0.28 ( r = 0.02) respectively), amount of cortical cataract ( P = 0.12 and P = 0.05 respectively), and amount of subcapsular posterior cataract ( P = 0.91 and P = 0.85 respectively). In a similar manner, the side difference in the presence of early AMD and late AMD was not significantly associated with the inter-eye difference in the presence of nuclear cataract ( P = 0.99 and P = 0.99 respectively), cortical cataract ( P = 0.25 and P = 1.00 respectively), and subcapsular posterior cataract ( P = 0.59 and P = 0.05 respectively). The side difference in the number of macular drusen was not significantly associated with the inter-eye difference in the amount of nuclear cataract ( P = 0.74), amount of cortical cataract ( P = 0.19) and amount of subcapsular posterior cataract ( P = 0.88). As a corollary, unilateral pseudophakia or aphakia was not significantly associated with inter-eye differences in the count ( P = 0.59) of drusen, and overall presence of early AMD ( P = 0.99) or late AMD ( P = 0.99). Conclusions In an intra-individual, inter-eye comparison, avoiding interdependencies of systemic parameters, inter-eye difference was not significantly associated with any characteristics of age-related macular degeneration in either any type of cataract or in pseudophakia. This suggests that the development of cataract or cataract surgery did not markedly influence the development of age-related macular degeneration.